2010
DOI: 10.5005/jp-journals-10018-1178
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Assessment of Dyspepsia in the Absence of Endoscopic Mucosal Lesions

Abstract: IntroductionDyspepsia is a common symptom with an extensive differential diagnosis. Endoscopy alone may miss serious mucosal lesions in about 15 to 30% of cases. The aim was to determine histopathological features of gastric and duodenal mucosal biopsies in patients with dyspepsia and normal looking upper gastrointestinal (GI) endoscopy.Materials and methodsOne hundred and five adult patients presenting with dyspepsia with no endoscopic mucosal lesions in the upper GI tract were included. Gastric biopsy specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
5
9
2
1
Order By: Relevance
“…Epigastric pain, morning vomiting and upper abdominal distention were more prevalent in H pylori positive cases than negative ones (Table 2). Our result was in agreement with other studies done in Egypt by Dawod and Emara, 2016 and in Sudan by Abdallah et al, 2014. In the present study we found that farmers acquire H pylori infection (82.1%) significantly more than nonfarmers (64.9%) ( Table 3). Also, farming occupation was associated with H pylori infection among 91.7% of dyspeptic patients in Ghana (Archampong et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Epigastric pain, morning vomiting and upper abdominal distention were more prevalent in H pylori positive cases than negative ones (Table 2). Our result was in agreement with other studies done in Egypt by Dawod and Emara, 2016 and in Sudan by Abdallah et al, 2014. In the present study we found that farmers acquire H pylori infection (82.1%) significantly more than nonfarmers (64.9%) ( Table 3). Also, farming occupation was associated with H pylori infection among 91.7% of dyspeptic patients in Ghana (Archampong et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study 81.7% of the patients had positive histopathological findings in esophageal biopsies associated with the dyspeptic symptoms. This finding is matching with the results reported by Dawod & Emara (4) and Nwokediuko & Okafor (27) ). This could be explained by the presence of other causes of inflammation than H. pylori or previous ingestion of antibiotics, which are known to suppress the H. pylori infection with a slow disappearance of chronic inflammatory cells (28) .…”
Section: Discussionsupporting
confidence: 93%
“…Despite Dyspepsia : is a common symptom, only 25% of patients with dyspepsia have an organic cause and up to 75% have functional dyspepsia (1) . The underline causes of dyspepsia included major causes as medications, functional dyspepsia, chronic peptic ulcer disease, and malignancy (4) . Other minor causes for dyspepsia include pancreatic disease, hepatobiliary tract disease, motility disorders, infiltrative diseases of the stomach, celiac disease, metabolic disturbances, diabetic neuropathy, and hernia (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] For example, Talebi-Taher et al, Ford et al, and Dawod and Emara in their studies found higher prevalence of dyspepsia in females than males. [16,19,20] In a Norwegian study of over 14,000 people, Johnsen et al found a significantly higher rate of FD in men compared with women (22.6 vs. 18.1%; P < 0.05). [21] A review done to study the epidemiology of uninvestigated FD in Asians revealed that there is no gender predilection.…”
Section: Discussionmentioning
confidence: 99%